The role of Notch-signalling in avian thymus and parathyroid glands development - Figueiredo, Marta Sofia Carvalho Teles de (2021)
The thymus generates central immune tolerance by producing self-restricted and self-tolerant T-cells, while the parathyroid glands regulate extracellular calcium homeostasis through the production of the parathyroid hormone (Pth). Despite their functional differences, they share a common endodermal origin in the pharyngeal region, which in avian corresponds to the endoderm of the 3rd and 4th pharyngeal pouches (3/4 PP). The involvement of several transcription factors and signalling pathways (including the Hedgehog pathway) during the early stages of thymus and parathyroid glands (T/PT) development has been reported over the years. However, the molecular mechanisms and interactions between major signalling pathways regulating their early development are still poorly understood. Namely, the potential contribution of Notch signalling – one of the major pathways involved in cell-fate determination and boundary formation – at these early stages remains unknown. Recently, and using the avian model, we observed the expression of Notch-related molecules in the presumptive territories of T/PT. In addition, during my master’s thesis I showed that the pharmacological inhibition of Notch signalling at these stages of T/PT development blocked Gcm2 (parathyroid marker) and altered Foxn1 (thymic marker) expressions, detected through in situ hybridization. These data suggest a potential role of Notch signalling during thymus and parathyroid glands early development. In addition, Notch and Hedgehog pathways have been shown to interact in several biological contexts. In this thesis, we investigated the role of Notch signalling at the early stages of T/PT development, and its possible interaction with Hedgehog in this context. Using the quail-chick developmental model and pharmacological inhibitors in vitro and in vivo, we show, for the first time, that Notch is crucial for T/PT common primordium development and for parathyroid formation. Notch signalling was found to be required (within a 48h time-window) for the normal expression of Foxn1 and Gcm2 at early stages of development. Moreover, Notch signals within this time-window were found to be crucial for parathyroid glands formation. We also show that Hedgehog acts upstream of Notch during T/PT early development. Hedgehog positively regulates the median domains of the pouch endoderm – the Gata3+/Gcm2+ anterior domain and the Lfng+ posterior domain – which seem to be more Hedgehog-responsive than the pouch tips, namely the dorsal tip where the thymus is formed. In addition, we provide evidence that the Lfng-expression domain is involved in the definition of the dorsal/posterior boundary of Foxn1/thymic rudiment. To clarify the tissue-specific role of Notch signalling at the early stages of T/PT development, isolated quail 3/4PP endoderm was electroporated with a Tol2-mediated gene transfer and tetracycline-dependent conditional expression system of vectors generated during my master thesis to induce loss- and gain-of-function of Notch signalling. A new loss-of-function construct (pT2K-NLS-Cherry-DNMAML1-eGFP) was also developed. However, the results obtained using the tested conditions were inconclusive, limiting the analysis of tissue-specific roles of Notch signalling in T/PT development during this thesis. This work provides new insights into the role of Notch signalling in T/PT early development, and into the interactions between major signalling pathways that regulate this development. However, which tissue – the endoderm or the surrounding mesenchyme – is the main driver of these Notch effects remains unanswered.